EW 104 EW against a new generation of threats - Adamy, David (The Artech House electronic warfare library, 2015)
The fourth book in the bestselling Artech House EW 100 series is dedicated to reviewing legacy threats and discussing new threats which have arisen since Y2K in communications, radar, and IR threats. Like its predecessors, EW 104 presents a series of highly informative and easy-to-comprehend tutorials, along with insightful introductory and connective material that helps you understand how each aspect fits together. This reference starts with a review of the generalities of legacy threats, from the technical point of view, with a focus on what makes the new threats more challenging. Readers are provided with details of threats in three major areas - Communications, Radars, and IR Threats. Market Engineers and managers responsible for designing or evaluating communications electronic warfare systems, government defense system procurement managers, and defense contractors.